Sea snakes (Serpentes: subfamilies Hydrophiinae and Laticaudinae) in Vietnam: a comprehensive checklist and an updated identification key - Rasmussen, Arne Redsted; Elmberg, Johan; Gravlund, Peter; Ineich, Ivan (Zootaxa, 2011)
Sea snakes (Elapidae, subfamilies Hydrophiinae and Laticaudinae) reach a very high species richness in Southeast Asia, but most countries in the region still lack comprehensive and up-to-date identification tools for these snakes. We present an updated checklist of sea snakes in Vietnam. We also provide diagnostic characters for all species and a new complete identification key, chiefly based on easy-to-use external characters. The checklist and key cover the 25 species documented from Vietnam, as well as three likely future additions to its sea snake fauna. By surveying incoming fishing vessels between Nha Trang and the mouth of Mekong River in 2000–2001, we were able to document two species new for Vietnamese waters: Hydrophis belcheri and H. pachycercos. Through these surveys we also secured four specimens of the rare endemic species H. parviceps, formerly known only from two specimens. A comprehensive bibliography of the literature treating sea snakes in Vietnamese waters is provided.Identification key: bibliography, biodiversity, diagnostic characters, Vietnamese waters